A traveler’s view on suggested attractions in Philippines: An adventure travel guide - Gayoso, Vicente S; Opriasa, Noel L (Journal of Tourism Management Research, 2025)
With the growing demand for adventure tourism, this study aimed to investigate travelers’ views regarding aspects in choosing suggested attractions in Guiuan, Eastern Samar, Philippines. The study, employing a descriptive quantitative approach, commences by identifying the participant profile and the factors that influence the selection of suggested attractions in Guiuan, Eastern Samar, Philippines. The researchers then validated security and safety, management, cleanliness and sanitation, and ambiance and environment as key factors in choosing the suggested attraction through surveys from the 241 tourists who visited attractions and sought adventure tourism in the area. The results revealed that the participants strongly agreed on all the factors in selecting the attractions. The study’s findings could help the attraction owners and managers improve their knowledge and skills in providing quality services and amenities, making them more attractive to visitors and resulting in repeat visits to their attractions, and provide beneficial insights into understanding the aspects that influence travelers’ views in selecting attractions in Guiuan, Eastern Samar. Lastly, the study developed a travel guide for tourists who seek adventure tourism. The researchers hope that this travel guide will boost the tourism industry in the municipality of Guiuan, Eastern Samar.